A randomized controlled trial of fentanyl in the pre‐emptive treatment of pain associated with turning in patients under mechanical ventilation: research protocol. (28th August 2014) - Robleda, Gemma; Roche‐Campo, Ferran; Urrútia, Gerard; Navarro, Marta; Sendra, Maria‐Àngels; Castillo, Ana; Rodríguez‐Arias, Ainhoa; Juanes‐Borrejo, Elena; Gich, Ignasi; Mancebo, Jordi; Baños, Josep‐E.
Abstract Aim To compare the effectiveness and safety of fentanyl with placebo as pre‐emptive treatment for pain associated with turning in patients in intensive care units. Background Turning is frequently a painful procedure in this setting. Pre‐emptive administration of supplementary analgesia may help decrease this pain. However, medical literature on pre‐emptive analgesia in these patients is scarce. Design A randomized, double‐blind, controlled clinical trial. Methods This study will assess the benefits and risks of pre‐emptive analgesia with fentanyl compared with placebo on turning‐associated pain. Eighty patients will be recruited from among those older than 18 years and needing mechanical ventilation for at least 24 hours. Pain intensity will be assessed using the Behavioral Pain Scale. Primary outcome will be pain intensity between the baseline and 30 minutes after turning, measured by the area under the curve of the pain scale scores. Secondary outcomes will be the usefulness of physiological parameters and the Bispectral Index to measure pain and the safety of pre‐emptive fentanyl in turning. The study protocol was approved in February 2011. Discussion If pre‐emptive fentanyl is more effective than placebo and reasonably safe, the results of the current study may change nursing attitude in managing turning in critically ill patients. As a consequence, pain may be decreased during this nursing procedure.